Compare the efficacy, safety and compliance of oral estradiol and vaginal estriol for urogenital problems in post-menopausal women - Kumari, Shipra; Singh, Monika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Menopause is recognised to have occurred after 12 months of amenorrhoea for which there are no obvious pathological and physiological causes, it is retrospective diagnosis. Objective of this study was to compare the efficacy, safety and compliance of oral estradiol and vaginal estriol for urogenital problems in post-menopausal women. Methods: A total of 100 postmenopausal women having urogenital symptoms were selected for the prospective study. The selected patients were randomly allocated in 2 groups. Group A received 2 mg of estradiol OD for 4 weeks and then evaluated after 4 weeks. Group B received 0.5 mg of vaginal estriol cream continuously for 4 weeks at night and then evaluated after 4 weeks. Patients were followed after 1,3 and 6 months. Inclusion criteria were postmenopausal women, vaginal symptoms, urogenital symptoms. exclusion criteria were all patients having estrogen dependent neoplasia and comorbidities. Results: For urinary complaints, symptomatic relief was assessed by AUA Score in which after 6 months; in Group A the difference in mean from baseline was 19.64±1.63 and in Group B it was 21±2.52 and was statistically insignificant from each other. For genital complaints, symptomatic relief was graded as 1, 2, 3, 4 in which grade 4 means complete relief. After 6 months of therapy 88.2% got complete relief in Group A and 91.1% in Group B. In vaginal cytological smears; in both groups, parabasal cells were reduced and superficial cells were increased after 6 months of therapy and both groups were statistically insignificant from each other. After 6 months of therapy, increase in mean value of KPI from the baseline is 24.54±10.1 in Group A and 28.6±10.11 in Group B and both groups were statistically insignificant. Endometrial thickness remained unchanged in both the groups after 6 months of therapy. Conclusions: Both drugs were equally effective in alleviating the urogenital symptoms with no significant side effects.